Penguatan Etika Kerja dan Budaya Kerja Digital dalam Meningkatkan Kualitas Layanan Berbasis Teknologi Informasi di Kecamatan Marga Punduh - Laras Retno Wulandharie; Muh. Ryan Rahmatullah Hidayat (Post Graduate School of Government Science, 2025)
This study aims to analyze the role of work ethics and digital work culture in improving the quality of information technology-based public services in Marga Punduh District, Pesawaran Regency. In the midst of the digital transformation of the public sector, challenges arise not only from technical aspects such as infrastructure and applications, but also from the readiness of human resources, especially in internalizing ethical values ïïand work patterns that are adaptive to technology. This study uses a qualitative descriptive approach with a case study strategy. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using thematic methods. The results of the study show that although the adoption of digital channels such as SIPDeskel and WhatsApp have been officially implemented, there are no clear internal regulations regarding digital ethics, personal data protection, and online service standards. The digital literacy of the apparatus is still limited and most employees have not received formal training related to the use of information systems. Digital work culture has also not been formed systematically; online collaboration and responsiveness are still individual and not standardized. This study offers novelty in emphasizing the importance of a value approach in the digital transformation of the public sector. Digital work ethics and technology-based work culture are not just complements, but the main foundations for ensuring the success and sustainability of digital public services. Therefore, digital public service reform needs to start from strengthening the values ïïand behavior of the apparatus, so that technology can be utilized optimally, ethically, and oriented towards the interests of the community.